Pembelajaran Inovatif Dengan Pendekatan Model Pembelajaran Quantum Learning Di Sekolah Dasar Dalam Peningkatan Kreativitas Berpikir Dan Hasil Belajar Siswa - Enjang Warman; Iis Ristiani (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This research was motivated by the queue and understanding of students in Indonesian learning activities in the classroom which was shown by the lack of student thinking activities in learning activities. The purpose of this study is to improve the creativity of thinking and the ability of grade VI students of SDN Gekbrong 1. The learning model used in this study is the Quantum Learning method. Quantum Learning is a research-based learning model that integrates the best teaching strategies with how students receive lessons. In this study, researchers apply the Quantum Learning method to Indonesian language learning The results obtained after applying the Quantum Learning method are an increase in thinking creativity and the ability of students in learning as evidenced by learning outcomes that reach an average of 90 and 94% learning completeness.  With the Quantum Learning Learning model, students are more active, creative and fun, because this method also contains elements of play while learning.